TRANSYLVANIAN JOURNAL OF TOURISM AND TERRITORIAL DEVELOPMENT. VOLUME 1 2015 - DOMBAY, István (Presa Universitară Clujeană, 2015)
During the socialist regime, investments in tourism in Maramures were oriented towards mountain leisure tourism, based on the abundantly available snow layer and curative tourism based on the saline waters of the old salt mines. Consequently, the mountain resorts of Borsa and Izvoare have appeared, the spa of Ocna Sugatag and the salty water strand of Costiui were developed, hence capturing the value of the salt lakes present in the abandoned salt mines.